2006
DOI: 10.1111/j.1539-6924.2006.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Insurability and Mitigation of Flood Losses in Private Households in Germany

Abstract: In Germany, flood insurance is provided by private insurers as a supplement to building or contents insurance. This article presents the results of a survey of insurance companies with regard to eligibility conditions for flood insurance changes after August 2002, when a severe flood caused 1.8 billion euro of insured losses in the Elbe and the Danube catchment areas, and the general role of insurance in flood risk management in Germany. Besides insurance coverage, governmental funding and public donations pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(165 citation statements)
references
References 17 publications
7
156
0
2
Order By: Relevance
“…In the light of these results it seems that physical flood mitigation measures and financial flood insurance policies are not seen as perfect substitutes, and indeed they partly cover different risks, as discussed before. Similar results (comparably high mitigation behaviour among insured households) are found in other studies for the German context (Thieken et al 2006) and in the USA for wind storm mitigation/insurance (Carson et al 2013;Chatterjee and Mozumder 2014;Petrolia et al 2013). …”
Section: Moral Hazard Effectssupporting
confidence: 77%
See 1 more Smart Citation
“…In the light of these results it seems that physical flood mitigation measures and financial flood insurance policies are not seen as perfect substitutes, and indeed they partly cover different risks, as discussed before. Similar results (comparably high mitigation behaviour among insured households) are found in other studies for the German context (Thieken et al 2006) and in the USA for wind storm mitigation/insurance (Carson et al 2013;Chatterjee and Mozumder 2014;Petrolia et al 2013). …”
Section: Moral Hazard Effectssupporting
confidence: 77%
“…For the Netherlands, Botzen et al report a higher self-reported willingness to invest in the elevation of a new house if the respondent is also willing to pay for flood insurance . For flood-prone areas in Germany, it seems that insured households take more private flood mitigation measures than non-insured, not less (Thieken et al 2006). Turning to the effect of expected government relief, some authors indeed report negative correlations with private mitigation (Botzen et al 2009;Grothmann and Reusswig 2006;Kreibich et al 2009).…”
Section: Literature Reviewmentioning
confidence: 95%
“…8 Botzen and van den Bergh (2008). 9 Thieken et al (2006 of flood insurance, the government also provided ad hoc disaster relief after several major flooding events, such as during the 2002 floods, which caused about h9.2 billion of damage. This government relief may reduce the demand for private insurance and it has been argued that the parallel administrative procedures of government relief and insurance after a flood can be time-consuming and inefficient.…”
Section: General Characteristicsmentioning
confidence: 99%
“…While several studies have found that increased knowledge and information correlate positively with precautionary behaviour (Thieken et al 2006, Miceli et al 2008, numerous studies found no evidence of a direct effect of information sources and flood adaptation behaviour when risk perception was controlled for (Zaleskiewicz et al 2002, Grothmann and Reusswig 2006, Botzen et al 2009). …”
Section: Protection Motivation Theory and Literature Reviewmentioning
confidence: 99%